The Link between HIV/AIDS and the Environment - Matiru, Violet; Osur, Joachim (My University, 2008)
Executive Summary It is estimated that 1.5 million people have died of HIV -related illnesses in Kenya since the first case was diagnosed in 1984. A total of 1.8 million children have been left orphans, and 1.4 million people are currently living with the disease. The high level of dependence of the majority o f Kenyans on natural resources means that they have turned to these same resources for solutions in the management of HIV/AIDS. This has therefore put additional pressure on the natural resource base. The study found that there are both direct and indirect linkages between HIV/AIDS and the environment/natural resources. Factors in the environment can either enhance or inhibit the spread of HIV. Malaria, that is endemic in some parts of Kenya, increases the transmission of HIV as do many sexually transmitted diseases. The study also shows that herbal medicine is widely used and reduces the risk of infection when used for sexually transmitted infections and febrile illnesses such as malaria. The herbs also slow down disease progre ssion when used to treat opportunistic infections. The same herbs can, however, lead to accelerated disease progression if not used properly such as when used in combination with ARVs or when preferred to ARVs. Unfortunately, the increased demand for herba l remedies is resulting in their over-exploitation and the threat of their extinction. Similarly, there has been an increased use of wild foods and timber due to the pandemic. Progression of disease is also accelerated by poor hygiene and sanitation which leads to the spread of infectious diseases among PLHIV. Poor disposal of HIV contaminated materials, such as condoms, syringes and home -based care kits poses a threat to communities, especially in the informal settlements in Kenya’s urban areas. The indirect linkages between HIV/AIDS and natural resources include the fact that areas with abundant natural resources tend to attract many people, including those who are running away from stigma due to their HIV status. The key sectors of fisheries, commercial agriculture and tourism tend to create conditions that make people more likely to get infected with the virus. Factors such as mobility, availability of cash and lack of social inhibitions due to distance from family in these sectors contribute to the spread of HIV. The HIV/AIDS pandemic has also had an impact on the land tenure systems of communities, while at the same time; some of the existing land tenure systems have put more people at risk of contracting HIV. When productive members of the household have passed on, the remaining members may lease the land or leave it fallow. Further, following the death of men from HIV, their widows are sometimes denied their rights to inherit the land and may be forced from the marital home. The sub-division of group ranches, and the subsequent sale of land that is registered under private title, has also contributed to the spread of HIV, as irresponsible land owners have used the money for alcohol and commercial sex. The impacts of HIV/AIDS on conservation have included the loss of staff and loss of the investment of training them, the cost of meeting medical bills and the cost of recruiting new staff. At the community level, the pandemic makes it difficult for agencies attempting to promote community conservation initiatives to do so, due to the heavy demands on the communities’ time to attend to the sick and bury the dead. In some cases, conservation efforts have put communities at risk of contracting HIV, such as when they have been evicted from forests and other conservation areas that previously served as their homes and sources of livelihood. Kenya HIV/AIDS and Environment Study 5 Rural-urban migration is sometimes prompted by the limited options available for rural communities to eke out a living from a degraded environment with poor soils due to over cultivation and grazing. People who travel to urban areas in search of employment are placed at risk of infection, which then makes them conduits through which the virus is introduced to the members of the community in their rural homes. Some of the existing initiatives to address issues arising from the linkages between HIV/AIDS and natural resources include projects to generate knowledge and share it with others. Several organizations and networks are involved in this, such as the African Biodiversity Collaborative Group (ABCG), the Population Reference Bureau (PRP), the Food and Agriculture Organization (FAO), the Swedish International Development Agency (SIDA), the Southern Africa Development Community (SADC) and the Coastal Resources Centre (CRC). These organizations have conducted surveys and produced research papers, toolkits and guidelines, aimed at addressing different issues related to HIV and NRM. Other initiatives are focused on tackling specific emerging issues, by assisting communities to develop more effective coping mechanisms. These include initiatives that target high risk groups within high risk sectors, by educating them on the risks and providing them with sustainable options for using natural resources to address their livelihood needs. At the organizational, national and international levels, policies are being formulated to tackle the HIV/AIDS issue and mainstream effective responses within different sectors, such as forestry, conservation, fisheries and land. Due to the complexity of the HIV/AIDS pandemic, with regard to the social and economic factors that contribute to its spread, it is important that a multi-sectoral approach is adopted when tackling specific concerns. It is therefore important to draw lessons from those communities and countries that have had success in different aspects of the issue, and up-scale and replicate these initiatives after analysing how they should be modified to suit the different social and cultural contexts.
Kenya HIV/AIDS and Environment Study
Keywords: HIV/AIDS; Natural resources; Sexually transmitted infections; ARVs; PLHIV; Forestry; Conservation; Economic factors